The impact of commodity prices, interest rate and exchange rate on stock market performance: An empirical analysis from Malaysia - Nordin, Norhafiza; Nordin, Sabariah; Ismail, Rusmawati (Universiti Utara Malaysia, 2014)
This paper examines the impact of commodity prices (palm oil price, oil price, and gold price), interest rate, and exchange rate on the Malaysian stock market performance. Employing the bounds test approach, the results of the study showed cointegrating relationships among variables. Specifically, the results revealed a significant influence of palm oil price on the stock market index.However, no significant influence was observed for both the oil price and gold price. Interest rate and exchange rate showed significant influences, which are consistent with past empirical studies.One important policy implication from this study is that the authorities should also pay attention to the effect of commodity prices, in addition to macroeconomic variables, in implementing relevant polices, as they may have a negative impact on the Malaysian stock market.